Seasonal Prevalence of Major Mastitis Pathogens Isolated from Crossbred Cow Milk Samples in Sub-tropical India (Indian Journal of Animal Production and Management, 2024)
The dairy industry suffers significant financial  losses due to mastitis. In order to control and  prevent mastitis, it is imperative to continuously  monitor the bacteriology, prevalence, and incidence  of major mastitis pathogens. Thus, the objective of  this research was to find out how often mastitis causing bacteria were isolated from milk samples of  crossbred cows over various seasons in India's  sub-tropical environment. 240 milk samples from 80  different cows were collected over the course of  three seasons [Hot Dry (April to June), Hot Humid  (July to September), and Autumn (October to  November)] in order to correlate the prevalence of  four main mastitis pathogens (Staphylococcus  aureus, Streptococcus agalactiae, Streptococcus  dysgalactiae, and Escherichia coli) with the season.  The most prevalent isolate during all seasons was  Staphylococcus aureus. Our findings demonstrated  a discernible relationship between seasonal  change and the isolation rate of the bacterium  associated with bovine mastitis, with the hot-humid  season having the greatest pathogen isolation rate.
Keywords: bacteriology; bovine mastitis; incidence; season